Dimension and Characteristic of Pragmatic Contextualism In Chinese Philosophy From Perspective of Confucianist and Daoist - Ayu Larasati (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2023)
“Science denialism”, which counters “science” with “science” to direct a “selected knowledge” has caused a “gap of truth” as in hoax that led to doubts of knowledge, which is a phenomenon of skepticism in the digital era. “Cartesian” verification of knowledge is limited because an algorithm-psychological-based “tool” can direct and utilize scientific data/values to support/negate knowledge for particular purpose regardless of objective truth. Thus, differentiation between truth and false needs to acknowledge the “qualitative reasoning”, as in pragmatic contextualism: a context-sensitive approach, exercised on local values-based actions as communication acts of “truth” and “false”. Pragmatic contextualism is practiced in Chinese philosophy, composed by “yin” and “yang” duality characteristics based on Confucius and Dao philosophy, which permeates into varied dimensions. Therefore, the paper aims to identify the characteristic and dimensions of pragmatic contextualism in Chinese philosophy from Confucianist and Daoist as an attempt to discover an alternative “verification” of “truth” on local values-based acts. The literature study from lectures, books, and articles (journals, news) is conducted to identify the characteristics and dimensions of pragmatic contextualism. The study founds the characteristics of pragmatic contextualism are personalization, relativity, holistic, multiscale, relationality, inter-spatiality, adaptivity, and plurality. Further, these characteristics are expressed in social, education, politic, spiritual, environment, aesthetics, and temporal dimension.